Quality of Telephone-Based Spoken Dialogue Systems - Möller, Sebastian (Springer US : Imprint: Springer, 2005)
Quality of Telephone-Based Spoken Dialogue Systems is a systematic overview of assessment, evaluation, and prediction methods for the quality of services such as travel and touristic information, phone-directory and messaging, or telephone-banking services. A new taxonomy of quality-of-service is presented which serves as a tool for classifying assessment and evaluation methods, for planning and interpreting evaluation experiments, and for estimating quality. A broad overview of parameters and evaluation methods is given, both on a system-component level and for a fully integrated system. Three experimental investigations illustrate the relationships between system characteristics and perceived quality. The resulting information is needed in all phases of system specification, design, implementation, and operation. Although Quality of Telephone-Based Spoken Dialogue Systems is written from the perspective of an engineer in telecommunications, it is an invaluable source of information for professionals in signal processing, communication acoustics, computational linguistics, speech and language sciences, human factor design and ergonomics.